Sistem Informasi Publik tentang Protokol Kesehatan Adaptasi Kebiasaan Baru di Universitas Brawijaya - Anggara, Azis Arief (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
University is one of the public spaces that have a high risk of COVID-19 transmission. These risks can be reduced with good information management, in which information management can be seen in the current information system. Brawijaya University has managed information about COVID-19 response, but the transmission risk is still high. The aim of this is to depicting the public information system on health protocols at Brawijaya University. The research use descriptive qualitative research method with spiral data analysis technique. The results showed that the existing information system consists of acquisition, production, storage, distribution and use of information. The findings showed that the existing public information system has not been able to provide a sense of urgency for the application of health protocols and the distribution channels used are not compatible with the distribution objectives.